2000
DOI: 10.1046/j.1365-2133.2000.03702.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory effects of dibutyryl cyclic adenosine monophosphate on cytokine production by keratinocytes and fibroblasts

Abstract: Background Clinical studies have shown that ointment containing dibutyryl cyclic adenosine monophosphate (DBcAMP) promotes wound healing.Objectives We aimed to elucidate the mechanisms of the beneficial effect of DBcAMP in wound healing. Methods An investigation was made of the effects of DBcAMP on in vitro cytokine release from cultured keratinocytes and fibroblasts derived from normal human skin. Results DBcAMP stimulated keratinocyte proliferation through increased interleukin (IL)-6 production by fibroblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 17 publications
0
9
2
Order By: Relevance
“…Our result is in conflict with a recent study of Zhou et al. who reported that dbcAMP significantly enhances fibroblast proliferation (10).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our result is in conflict with a recent study of Zhou et al. who reported that dbcAMP significantly enhances fibroblast proliferation (10).…”
Section: Discussioncontrasting
confidence: 99%
“…Because in the study of Zhou et al. dbcAMP was shown to stimulate the production of TGF‐β by fibroblast (10), it cannot be excluded that the proliferative effect of dbcAMP they observed could be mediated by an autocrine effect of TGF‐β on fibroblasts themselves. If this should be the case, TGF‐β production could not be occurred in our cultures, where fibroblasts were grown in serum‐free medium 24 h before and during the treatment with PTHrp.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…PGE1 ointment was effective in treating patients with incurable peripheral ischaemic ulcers (34) and burn patients presenting rapid epithelialisation (11). DBcAMP stimulated the growth of keratinocytes and fibroblasts by inducing secretion of several cytokines (35,36), and its topical application resulted in significant acceleration of wound healing in an animal model (12). Clinical study of this ointment has also shown its benefits in the treatment of pressure ulcers (37).…”
Section: Discussionmentioning
confidence: 99%